2013
DOI: 10.1016/j.appet.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of the responsiveness to child feeding cues scale

Abstract: Parent-child feeding interactions during the first two years of life are thought to shape child appetite and obesity risk, but remain poorly studied. This research was designed to develop and assess the Responsiveness to Child Feeding Cues Scale (RCFCS), an observational measure of caregiver responsiveness to child feeding cues relevant to obesity. General responsiveness during feeding as well as maternal responsiveness to child hunger and fullness were rated during mid-morning feeding occasions by 3 trained c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 57 publications
4
94
3
5
Order By: Relevance
“…This supports observations reported by Hodges et al (2013) in their development of the Responsive to the Child Feeding Cues Scale (RCFCS) in which 20 hunger cues were identified (engagement) compared to 28 satiation cues (disengagement). Eight cues were removed from the analysis in this study as they appeared infrequently.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This supports observations reported by Hodges et al (2013) in their development of the Responsive to the Child Feeding Cues Scale (RCFCS) in which 20 hunger cues were identified (engagement) compared to 28 satiation cues (disengagement). Eight cues were removed from the analysis in this study as they appeared infrequently.…”
Section: Resultssupporting
confidence: 75%
“…According to Hodges et al (2013) there are several observational tools to measure feeding interactions in early infancy but these have most often been used to identify eating pathology and were therefore not suitable for the present study. This study is based on the work of Dr. Kathryn Barnard and her colleagues who developed the child health assessment model to determine predictors that could identify children at risk for later developmental problems (Barnard and Eyres.…”
Section: Procedurementioning
confidence: 98%
“…In a Finnish study, babies born large for gestational age were more likely found to be obese young adults 21 . Maternal responsiveness studies found that mothers were more responsive to child hunger than fullness clues 22 . This is consistent with the relation between appetite and BMI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that the prominence, intensity and specificity of infant cues guided decisions about initiating and ending feeds and that mothers found cues easier to interpret with increasing infant age. Hodges et al (2013) went on to develop a tool to characterise and code responsive feeding. The…”
Section: Accepted Manuscriptmentioning
confidence: 99%